Response of growth and yield attributes of sorghum to foliar nano-nitrogen fertilization - Rahul Gautam; O.P. Sharma; Nikhil Gauttam; J.K. Sharma (Annals of Agricultural Research, 2025)
A field experiment was conducted during kharif 2024 at the Agronomy Farm, School of Agriculture, Suresh Gyan Vihar University, Jaipur, to study the effect of foliar application of nano nitrogen fertilizer on growth and yield of sorghum (Sorghum bicolor L.). The experiment was laid out in a randomized block design with three replications, comprising nine treatments viz., T1 (Control), T2 (75% RDN with commercial urea in two equal splits), T3 (75% RDN + nano urea foliar spray in two equal splits at 20 and 40 DAS), T4 (75% RDN + nano urea foliar spray in three equal splits at 15, 30 and 45 DAS), T5 (100% RDN with commercial urea in two equal splits), T6 (100% RDN + nano urea foliar spray in two equal splits), T7 (100% RDN + nano urea foliar spray in three equal splits), T8 (125% RDN + nano urea foliar spray in two equal splits) and T9 (125% RDN + nano urea foliar spray in three equal splits). The sorghum variety ‘Parbhani Shakti’ was sown at a spacing of 45 cm × 15 cm using a seed rate of 15 kg ha-1 with a recommended dose of fertilizer (80:40:40 NPK kg ha-1). The results revealed that growth attributes such as plant height, dry matter accumulation, leaf area index and tiller number improved significantly with higher nitrogen application and nano urea sprays. The maximum plant height (197.3 cm) and dry matter accumulation (162.5 g plant-1) were observed under T5, whereas the highest leaf area index (5.7) was recorded under T9, highlighting the efficiency of nano urea in sustaining photosynthetic activity. Yield attributes also showed significant variation, the highest grain yield (2768 kg ha-1), straw yield (6203 kg ha-1) and biological yield (8971 kg ha-1) were obtained with T5, closely followed by T9 (2683, 6074 and 8757 kg ha-1, respectively).